ANALISIS HASIL BELAJAR PADA MODEL PEMEBLAJARAN KOOPERATIF TIPE JIGSAW PADA PEMBELAJARAN IPA KELAS IV SD NEGERI 1 WIDODO - Intan Dwi Aistina; Firdha Maharani; Episiasi Episiasi (CV. ADIBA ASIHA AMIRA, 2025)
Education aims to help students achieve maturity through effective interaction. Science learning emphasizes environmental understanding through observation and experimentation. The jigsaw cooperative model facilitates active interaction in small groups. This study evaluates the jigsaw model's application in fourth-grade science learning at SD Negeri 1 Widodo using a qualitative approach with observation, interviews, and documentation. The findings reveal that teaching steps were well-implemented, improving students' motivation, participation, and learning outcomes, with 24 out of 26 students achieving good to excellent scores. The jigsaw model effectively fosters a cooperative and enjoyable learning environment